A multiscale approach to the adsorption of core–shell nanoparticles at fluid interfaces. Issue 1 (5th November 2014) - Nelson, Adrienne; Wang, Dapeng; Koynov, Kaloian; Isa, Lucio
Abstract : Multiscale characterisation highlights the unique behaviour of soft, core–shell nanoparticles at fluid interfaces. Abstract : Self-assembly of colloidal particles at liquid–liquid interfaces is a process with great potential for the creation of controlled structures, due to the trapping of the particles in the plane of the interface combined with their lateral mobility. Here we present a multiscale characterisation of the adsorption and interfacial behaviour of core–shell iron oxide–poly(ethylene glycol) nanoparticles at a water– n -decane interface using three complementary, in situ, methods, which span many different length scales. First, dynamic interfacial measurements are taken to follow the adsorption of particles from the bulk aqueous phase to the interface. The mechanical properties of the interface are then probed using micron-sized tracers in probe-particle tracking and nano-tracers in fluorescence correlation spectroscopy. The results show that the rate of particle adsorption to the interface scales with the square of bulk concentration, as predicted by a recent model. In addition, we show that despite full monolayers of nanoparticles forming, the interface remains unexpectedly fluid, with only a slowing of tracer particle mobility but no evidence of interface jamming as seen for hard nanoparticles. Our results illustrate that nanoparticles stabilised by soft, extended polymeric shells, display distinct features at fluid interfaces that can be harnessed for the fabrication of functional materials.